Validação de instrumento de avaliação por competências de discentes de enfermagem no cenário hospitalar - Ramos, Stéphannie Lynne Torres Costa (2021)
The National Curricular Guidelines (DCN) for undergraduate courses in the health area were instituted in 2001 and aimed to guide the process of reorienting the training of profesionals follwing the principles of SUS and establishing the general and specific competences to be developed. It is of great relevance to search for new teaching models, focused on the commitment to training and the skills and requirements demanded in the job market. There is, then, a growing discussion about competence-based education, however, it is observed that the evaluation processo f students during the internship field does not take place clearly, with well-defined objectives, explicit requirements, witch makes the process more difficult, since theres is no standardization of these evaluation processes. This study aimed to validate a competency assessment instrument that contributes to the improvement os teaching-learning assessment of nursing studnts in the hospital practice setting. This was a methodological study with quantitative and qualitative approach, whose steps included the review of previous studies, elaborations of an instrument and tha obtaining of consensus by Delhpi technique in two rounds, with subsequente analysis by specialist and reliability through Cronachs’s alpha and calculation of the CVI. From the values obtained, it was found that the instrument has lost stability and has proves to be reliable, clear and relevant. A pilot test was carried out wiht teacher, nurses of the discipline and the students and, based on the contente alnaysis of the answers, revealed that their perceptions was that the instrument has good applicability in the evaluative practice of the discipline offered in the Bursing course of a public university of the state of Ceará- Brazil. It is conidered that the instrument can contirbute to improving the assessment of nursing students’ learning and, consequently, to the training of future professional and improving the quality of health care.